EFFECT OF USE OF DERIVATIVE SNAKE TEACHING AIDS ON MATHEMATICS LEARNING OUTCOMES - Muhammad Arif Satria Nasution; Herman Mawengkang; Mardiningsih Mardiningsih (JISTech (Journal of Islamic Science and Technology), 2018)
This study aims to determine the effect of student learning outcomes using snake props derived from derivative material functions in class XI of SMA 1 Meranti. The study sample was determined randomly and there were 4 classes available so the study population consisted of 2 classes, each of which consisted of 34 students and XI Science-1 experimental class and class XI Science-2 control class. The test instruments in this study consisted of 5 questions essay tests. From the data analysis the average and standard deviation in the experimental class were obtained to pretest 46,471 and 10,282, while for posttest 74,00 and 10,708. For the average value and standard deviation of the control class to pretest 43,059 and 10,790 and posttest data 66,471 and 10,329. From the data analysis using the t-test at the level of α = 0.05, obtained tcount = 2.951 for t table = 1.668 it turns out ttable < t1-α, then H0 is rejected and Ha is accepted. Thus the conclusion is that there is an influence of student learning outcomes using snake props derived from derivative material functions in class XI of SMA 1 Meranti.